Correlation Of Knowledge Level With Pain Management In Elderly With Osteoarthritis - I Gede Yudiana Putra; Ni Made Sri Muryani; Putu Intan Daryaswanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background: Pain is the most common symptom felt by the elderly with osteoarthritis. Poor management of pain would impact their health status and quality of life in the end. Therefore, an adequate level of knowledge required to manage this pain properly. This study aimed to examine the correlation of knowledge level and pain management in the elderly population with osteoarthritis in WanaSraya Nursing Home. Method: . This study applied an analytic observational design with a cross-sectional approach to examine the correlation between the knowledge level and pain management in the elderly. Research participants that involved a total of 30 respondents selected by the total sampling technique.In this study using a questionnaire.Data analysis was carried out by using bivariate data analysis test using Pearson Correlation Test. Result: The study result showed that the majority of the respondent has a good level of knowledge related to osteoarthritis and pain management. Pearson Correlation Test with the degree of significance of p less than 0.05 revealed that the p-value was 0.000. Conclusion: There was a correlation between the level of knowledge with pain management in elderly with osteoarthritis.